RISK OF ADVERSE OUTCOMES IN HOSPITALIZED PATIENTS WITH AUTOIMMUNE DISEASE AND COVID-19: A MATCHED COHORT STUDY FROM NEW YORK CITY. (21st January 2021) - Faye, Adam; Lee, Kate; Laszkowska, Monika; Kim, Judith; Blackett, John; McKenney, Anna; Krigel, Anna; Giles, Jon; Wang, Runsheng; Bernstein, Elana; Green, Peter; Krishnareddy, Suneeta; et al.
Abstract: Objective: To examine the impact of autoimmune disease on the composite outcome of intensive care unit admission, intubation, or death, from COVID-19 in hospitalized patients. Methods: Retrospective cohort study of 186 patients hospitalized with COVID-19 between March 1 st –April 15 th, 2020 at New York-Presbyterian Hospital/Columbia University Irving Medical Center. The cohort included 62 patients with autoimmune disease and 124 age- and sex- matched controls. The primary outcome was a composite of intensive care unit admission, intubation, and death, with secondary outcome assessing time to in-hospital death. Baseline demographics, comorbidities, medications, vital signs, and laboratory values were collected. Conditional logistic regression and Cox proportional hazards regression were used to assess the association between autoimmune disease and clinical outcomes. Results: Patients with autoimmune disease were more likely to have at least one comorbidity (25.8% vs. 12.9%, p =0.03), take chronic immunosuppressive medications (66.1% vs. 4.0%, p<0.01), and have had a solid organ transplant (16.1% vs. 1.6%, p <0.01). There were no significant differences in intensive care unit admission (14.2% vs. 19.4%, p= 0.44), intubation (14.2% vs. 17.7%, p =0.62) or death (17.5% vs. 14.5%, p =0.77). On multivariable analysis, patients with autoimmune disease were not at an increased risk for a composite outcome of intensive care unit admission, intubation, or death (adj OR 0.79, 95%CI 0.37–1.67). On Cox regression, autoimmune disease was not associated with in-hospital mortality (adj HR 0.73, 95%CI 0.33–1.63). Conclusion: Among patients hospitalized with COVID-19, individuals with autoimmune disease did not have an increased risk of a composite outcome of intensive care unit admission, intubation, or death. Kaplan-Meier curve examining death, stratified by the presence or absence of autoimmune disease in all 186 patients, with 16 patients censored as of 4/29/2020